A Morphometric Analysis of Commonly Used Craniometric Approaches for Freehand Ventriculoperitoneal Shunting. Issue 2 (February 2022) - Woo, Peter Y. M.; Wong, Desiree K. K.; Yuan, Yixuan; Guo, Xiaoqing; See, Michael K. W.; Tam, Matthew; Wong, Alain K. S.; Chan, Kwong-Yau
Abstract : BACKGROUND: Ventricular catheter tip position is a predictor for ventriculoperitoneal shunt survival. Cannulation is often performed freehand, but there is limited consensus on the best craniometric approach. OBJECTIVE: To determine the accuracy of localizing craniometric entry sites and to identify which is associated with optimal catheter placement. METHODS: This is a retrospective analysis of adult patients who underwent ventriculoperitoneal shunting. The approaches were categorized as Kocher's, Keen's, Frazier's and Dandy's points as well as the parieto-occipital point. An accurately sited burr hole was within 10 mm from standard descriptions. Optimal catheter tip position was defined as within the ipsilateral frontal horn. RESULTS: A total of 110 patients were reviewed, and 58% (65/110) of burr holes were accurately sited. Keen's point was the most correctly identified (65%, 11/17), followed by Kocher's point (65%, 37/57) and Frazier's point (60%, 3/5). Predictors for accurate localization were Keen's point (odds ratio 0.3; 95% CI: 01-0.9) and right-sided access (odds ratio 0.4; 95% CI: 0.1-0.9). Sixty-three percent (69/110) of catheters were optimally placed with Keen's point (adjusted odds ratio 0.04; 95% CI: 0.01-0.67), being the only independent factor. Thirteen patients (12%) required shunt revision at a mean duration of 10 ± 25 mo. Suboptimal catheter tip position was the only independent determinant for revision (adjusted odds ratio 0.11; 95% CI: 0.01-0.98). CONCLUSION: This is the first study to compare the accuracy of freehand ventricular cannulation of standard craniometric entry sites for adult patients. Keen's point was the most accurately sited and was a predictor for optimal catheter position. Catheter tip location, not the entry site, predicted shunt survival.